Why Are There Rich and Poor Countries? Symmetry Breaking in the World Economy: A Note. - Ioannides, Yannis Menelaos. (Tufts University. Tisch Library., 2016)
This paper extends Matsuyama (1996) to allow for the presence of a fixed factor such as land. By assuming that agricultural production is more land-intensive than manufacturing production, we generalized Matsuyama's results on symmetry breaking in the world economy. That is, international trade by causing an agglomeration of economic activities in different countries of the world makes inevitable the coexistence of Rich and Poor.